Sinergi New Public Management dan New Public Service Dalam Pengelolaan Sumber Daya Air Dinas Pekerjaan Umum dan Tata Ruang Kabupaten Bolaang Mongondow Selatan di Era Digital - Suja, Siti Fatima; Isa, Rusli (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The digital transformation in public administration has created new challenges for local technical agencies, including the Public Works and Spatial Planning Office (PUTR), which plays a crucial role in water resources management (WRM). This study analyzes the synergy between the New Public Management (NPM) paradigm—focused on efficiency and performance—and the New Public Service (NPS) paradigm—emphasizing participation and public value—in the management of WRM at the PUTR Office of Bolaang Mongondow Selatan Regency, Indonesia. A qualitative descriptive method was applied through literature review, limited interviews with PUTR officials, and policy document analysis. The findings reveal that digitalization initiatives such as GIS-based irrigation network monitoring, damage reporting applications, and e-supervision systems have improved efficiency and accountability (NPM principles). However, program sustainability depends heavily on community collaboration, farmer associations, and local user groups (NPS principles). The synergy between NPM and NPS creates a hybrid model of public administration that is both efficient and inclusive, reinforcing good water governance in the digital era.